Do Special Tax Regimes for Micro and Small Enterprises Encourage Formal Firm Creation? : Do They Lead Firms to Underreport Revenues? - Bruhn, Bruhn; Loeprick, Jan (World Bank, Washington, DC, 2016)
This note highlights research using administrative data from the Georgian Tax Authority to estimate the effects of special tax regimes for micro and small enterprises on formal firm creation and tax compliance. This work was carried out under the Investment Climate Impact Program.